Effects of pre-soaked zeolite and CaO-based expansive agent on mechanical properties and autogenous deformation of early-age concrete. (20th November 2020) - Zhao, Haitao; Li, Jinghao; Sun, Gaoyang; Jiang, Jianhua; Xuan, Weihong; Chen, Yuzhi; Tian, Qian; Liu, Jiaping
Highlights: Effects of zeolite and CEA on mechanical properties of concrete are investigated. Effects of zeolite and CEA on IRH of concrete are studied. Effects of zeolite and CEA on autogenous deformation of concrete are evaluated. Synergistic mechanism of zeolite and CEA on AS mitigation of concrete is analysed. Abstract: High-performance concrete (HPC) is prone to cracking at an early age due to the large autogenous shrinkage (AS), which severely weakens the durability of the concrete structure. CaO-based expansive agent (CEA) is widely utilized to compensate for the AS of HPC, but CEA cannot achieve its potential expansion in HPC due to a low water to binder ratio, resulting in an incomplete hydration, and a sharp and substantial retraction after initial expansion. Pre-soaked zeolite can be introduced as internal curing (IC) agent to reduce the AS of HPC owing to the IC water released from zeolite. According to the AS-reduction mechanism of CEA and zeolite, a synergistic mechanism can be achieved by the combination use of CEA and zeolite in HPC. However, a comprehensive understanding of the effects of the combination use of zeolite and CEA on the mechanical properties and autogenous deformation of concrete is still lacking. Therefore, the influence of zeolite and CEA addition on mechanical properties and autogenous deformation were investigated experimentally. The investigation results showed that the zeolite addition weakened the mechanical properties of concrete while the CEA addition had the opposite effect. The internal relative humidity in concrete was significantly improved with zeolite and CEA incorporation. The IC water released from zeolite could not only enhance the expansion efficiency at an early age but also greatly reduce the retraction at the later age. The results exhibited an obvious synergistic mechanism with the combination use of zeolite and CEA on AS mitigation, which is of great benefit in AS-induced cracking control.